Stability of wheat grain yields over three field seasons in the UK. (19th September 2018) - Pennacchi, João Paulo; Carmo‐Silva, Elizabete; Andralojc, P. John; Lawson, Tracy; Allen, Alexandra M.; Raines, Christine A.; Parry, Martin A. J.
Abstract: Ensuring food security in a changing climate is a major contemporary challenge and requires development of climate‐resilient crops that perform well under variable environments. The hypothesis that yield stability in suboptimal conditions is linked to yield penalties in optimal conditions was investigated in field‐grown wheat in the UK. The phenotypic responses, rate of wheat crop development, and final grain yield to varying sowing date, rainfall, air temperature, and radiation patterns were studied for a panel of 61 elite commercial wheat cultivars grown in the UK in 2012, 2013, and 2014. Contrasting climatic patterns, particularly rainfall accumulation and distribution over the season, influenced the relative performance of the cultivars affecting the duration of grain development stage and impacting on productivity. Indices for crop productivity, yield stability, and performance under suboptimal conditions revealed four cultivars with a combination of stable and high relative grain yields over the three seasons: Gladiator, Humber, Mercato, and Zebedee. Genetic similarity between cultivars partially explained yield performance in the contrasting seasons. The year of release of the cultivars correlated with grain yield but not with yield stability, supporting the contention that breeding for yield potential does not select for climate resilience and yield stability of crops. Further analysis of the outstanding cultivars may unravel target traits for breeding efforts aimed at increasing wheat yield potential and stability in the changing climate. Abstract : Crop development and final grain yield were studied in 61 wheat cultivars over three consecutive field seasons, characterized by markedly different climatic conditions. Indices were determined for crop productivity, yield stability, and performance under suboptimal conditions. Combined analysis of the results obtained revealed four cultivars with stable and high relative grain yields over the three seasons: Gladiator, Humber, Mercato, and Zebedee.